2015
DOI: 10.1103/physreve.91.043305
|View full text |Cite
|
Sign up to set email alerts
|

Boundary condition for lattice Boltzmann modeling of microscale gas flows with curved walls in the slip regime

Abstract: The lattice Boltzmann method (LBM) has been widely used to simulate microgaseous flows in recent years. However, it is still a challenging task for LBM to model that kind of microscale flow involving complex geometries, owing to the use of uniform Cartesian lattices in space. In this work, a boundary condition for microflows in the slip regime is developed for LBM in which the shape of a solid wall is well considered. The proposed treatment is a combination of the Maxwellian diffuse reflection scheme and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
0
54
1
Order By: Relevance
“…Most recently, a curved slip BC based on the DBB method has been proposed , which performs well in the simulations of microflow with complex boundaries. Therefore, it is adopted in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, a curved slip BC based on the DBB method has been proposed , which performs well in the simulations of microflow with complex boundaries. Therefore, it is adopted in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is adopted in the present study. In this curved DBB scheme , the unknown distribution function that comes from the solid wall at a boundary node is specified as: true fi = rf i ¯ + +(1-r) fi normaleq …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So the BSR scheme is not enough for the simulation of liquid flow. The DBB scheme has more potential in the simulation of fluid flows with complex geometries for the 115 nature of its local calculations [37,38]. However, few simulations employed the DSR and DBB schemes for liquid flow.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3. This boundary condition is firstly applied by Lim et al [91] to investigate pressure driven and shear driven micro-channel flows, however, it was found that the mesh size has a significant effect on the numerical results in their work [91][92] and pure specular reflection may overestimates the slip velocity [93]. Figure 3: Illustration of the reflection process (in the left image, the distributions before the collision are highlighted.…”
Section: Specular Reflection Boundary Condition(sr)mentioning
confidence: 99%